English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I know you've got to put them into (x(+-))(x(+-))... but I can't remember what order to do that in.

2007-09-18 06:46:02 · 4 answers · asked by em.four 2 in Science & Mathematics Mathematics

It would help if I wrote the problem correctly huh?
x^2-1x-2

2007-09-18 06:54:38 · update #1

4 answers

Not surprising, seeing as you can't factor that expression :P

EDIT : It's not (x+1)(x-2), because that gives you x^2 - x - 2

2007-09-18 06:51:22 · answer #1 · answered by rahidz2003 6 · 0 0

x^2-1x+2= x= 0.5 plus or minus the square root of 1.75

2007-09-18 07:39:38 · answer #2 · answered by Will 4 · 0 0

Ah, now that you rewrote it it makes it easier. :)

x^2 - x - 2
= x^2 + x - 2x - 2
= x * (x + 1) - 2 * (x + 1)
= (x + 1) * (x - 2).

2007-09-18 07:08:00 · answer #3 · answered by RustyL71 4 · 0 0

x^2 -x + 2 =

x^2 - 2(1)(1/2)x + (1/2)^2 - (1/2)^2 + 2 =

(x - 1/2)^2 + 2 - 1/4 =

(x - (1/2)^2 + 7/4 =

(x - (1/2)^2 - (i^2)7/4

[(x - 1/2)]^2 - [(sqrt(7) (i)/2]^2 =

[x -1/2 +(i/2) sqrt(7)][x -1/2 - i/2)sqrt(7)]

since a^2 - b^2 = (a+b))(a-b)

2007-09-18 07:07:14 · answer #4 · answered by mohanrao d 7 · 0 0

fedest.com, questions and answers